1978
DOI: 10.1093/jnci/60.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Human Urogenital Tract Tumors for Papovavirus Etiology: Brief Communication 2

Abstract: Cells cultured from human urogenital cancer and other cancers as well as cells from noncancerous tissues were examined by immunofluorescent staining with antibodies to T-antigens and capsid antigens of papovaviruses BK virus (BKV), JC virus, and simian virus 40(SV40), and to capsid antigens of herpes simplex virus types 1 and 2 and human cytomegalovirus (CMV). Cells from early passage cultures of 123 primary tissues and from 14 continuous lines derived from transitional or renal cell carcinoma were tested. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…These results are in accord with those of a previous study, which also reported negative results for bladder cancer (Shah et al, 1978). Lack of BK virus protein does not exclude the possibility that viral DNA is present, although previous studies designed to identify BK virus genomes in normal prostate tissue and in prostate cancer cells have produced inconsistent results and are difficult to interpret (Zambrano et al, 2002;Das et al, 2004).…”
Section: Sirsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in accord with those of a previous study, which also reported negative results for bladder cancer (Shah et al, 1978). Lack of BK virus protein does not exclude the possibility that viral DNA is present, although previous studies designed to identify BK virus genomes in normal prostate tissue and in prostate cancer cells have produced inconsistent results and are difficult to interpret (Zambrano et al, 2002;Das et al, 2004).…”
Section: Sirsupporting
confidence: 88%
“…Only one published study has reported finding SV40 T antigen present in tumour tissue (but not in adjacent normal tissue), but this was an unusual case in an immunosuppressed transplant recipient (Geetha et al, 2002). Studies of bladder cancer in immunocompetent people have not found SV40 T antigen (Shah et al, 1978). BK virus DNA has been identified in papillary urothelial bladder carcinoma in one study (Monini et al, 1995).…”
Section: Sirmentioning
confidence: 92%
“…Fifteen out of the twenty-five articles met the criteria by using the molecular-based techniques for the detection of BKV DNA or proteins in tissues. The other ten were excluded for the following reasons: reviews (n=3) [44-46], serological studies (n=3) [47-49], case report (n=1) [50], comment (n=1) [51], cell line study (n=1) [52] or publication in language other than English (n=1) [53]. Out of the fifteen articles included in the analysis, eight were carried out in Europe (Italy [54-56], Switzerland [57], UK [58], Sweden [59], Greece [60], Germany [61]), five in USA [9, 31, 62-64], one in Mexico [65] and one in Japan [66].…”
Section: Bkv-dna Expression In Cancer Specimens: Original Reports Agamentioning
confidence: 99%
“…Some earlier studies using immunofluorescent staining for TAg or DNA hybridization analyses on tumor samples or cells derived from tumors did not identify a link between BKV and various urogenital carcinomas [69,70]. More recent reports, however, tend to point to the participation of BKV in the pathogenesis of these tumors, possibly due to improvements in the detection methods.…”
Section: Bk Virus and Human Tumorsmentioning
confidence: 99%